Chronic AdipoRon Treatment Mimics the Effects of Physical Exercise on Restoring Hippocampal Neuroplasticity in Diabetic Mice - Thomas H Lee; Ahadullah; Brian R Christie; Kangguang Lin; Parco Ming-fai Siu; Li Zhang; Ti-fei Yuan; Pragya Komal; Aimin Xu; Kwok-fai So; Suk-yu Yau (Molecular Neurobiology, 2021)
Administration of exercise mimetic drugs could be a novel therapeutic approach to combat comorbid neurodegeneration and metabolic syndromes. Adiponectin is an adipocyte-secreted hormone. In addition to its antidiabetic effect, adiponectin mediates the antidepressant effect of physical exercise associated with adult hippocampal neurogenesis. The antidiabetic effect of the adiponectin receptor agonist AdipoRon has been demonstrated, but its potential pro-cognitive and neurotrophic effects in the hippocampus under diabetic condition are still unclear. This study reported that chronic AdipoRon treatment for 2 weeks improved hippocampal-dependent spatial recognition memory in streptozotocin-induced diabetic mice. Besides, AdipoRon treatment increased progenitor cell proliferation and neuronal differentiation in the hippocampal dentate gyrus (DG) of diabetic mice. Furthermore, AdipoRon treatment significantly increased dendritic complexity, spine density, and N -methyl-D-aspartate receptor-dependent long-term potentiation (LTP) in the dentate region, and increased BDNF levels in the DG of diabetic mice. AdipoRon treatment activated AMPK/PGC-1α signalling in the DG, whereas increases in cell proliferation and LTP were not observed when PGC-1α signalling was pharmacologically inhibited. In sum, chronic AdipoRon treatment partially mimics the benefits of physical exercise for learning and memory and hippocampal neuroplasticity in the diabetic brain. The results suggested that AdipoRon could be a potential physical exercise mimetic to improve hippocampal plasticity and hence rescue learning and memory impairment typically associated with diabetes.